2016
DOI: 10.1098/rsob.160229
|View full text |Cite
|
Sign up to set email alerts
|

A decision underlies phototaxis in an insect

Abstract: Like a moth into the flame—phototaxis is an iconic example for innate preferences. Such preferences probably reflect evolutionary adaptations to predictable situations and have traditionally been conceptualized as hard-wired stimulus–response links. Perhaps for that reason, the century-old discovery of flexibility in Drosophila phototaxis has received little attention. Here, we report that across several different behavioural tests, light/dark preference tested in walking is dependent on various aspects of fli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 77 publications
1
40
1
Order By: Relevance
“…The known phototaxis behavior in Lymnaea 7 seems also to be unaffected by the internal state (preceding motor load). 5 Our results contrast with recently reported finding on another invertebrate, the fruit fly Drosophila melanogaster , 8 where phototaxis was controlled by internal cues. Thus, we conclude that light conditions immediately preceding the test can be discarded as a key factor influencing the decision-making process of snails in our experiments.…”
contrasting
confidence: 99%
“…The known phototaxis behavior in Lymnaea 7 seems also to be unaffected by the internal state (preceding motor load). 5 Our results contrast with recently reported finding on another invertebrate, the fruit fly Drosophila melanogaster , 8 where phototaxis was controlled by internal cues. Thus, we conclude that light conditions immediately preceding the test can be discarded as a key factor influencing the decision-making process of snails in our experiments.…”
contrasting
confidence: 99%
“…As is known, phototaxis is a type of directional locomotory movement that occurs when a living organism moves toward or away from a light source. It typically occurs in certain living organisms, such as insects, jellyfish, or zooplankton, that are considered to be related to navigation or photosynthesis 65,66. Very recently, Zhao et al reported a swimmer robot based on a photosensitive hydrogel oscillator showing negative phototactic movement (away from the light source) in water driven by a laser 4.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, these two biogenic amines differently modulate phototaxis, in what it seems to be a goal-directed or value-based decision-making process. Phototaxis seems to be a special case of photopreference and manipulating the ability of flies to fly can reversibly shift it from approach to avoidance in walking flies (Gorostiza et al, 2016 ). Photopreference can be influenced by the shape, form, or degree of intactness of the wings, the ability of flies to move them, and the state of sensory organs related to flight.…”
Section: Behavioral Plasticity and The Stimulus–response Modelmentioning
confidence: 99%